Absorptive capacity: A process and structure approach. (February 2019) - Vasconcelos, Ana Cristina; Martins, Jorge Tiago; Ellis, David; Fontainha, Elsa
The aim of this study is to understand and explain different dimensions of absorptive capacity and the strategies used in practice to realise it. The theoretical and conceptual contribution of the study lies in the adoption of a dual process and structure approach, aiming at identifying, respectively, how learning takes place and what learning takes place. The study is based upon a case study research design to explore the manifestation of absorptive capacity processes and its relationship to knowledge structures in four company case studies. The findings of the research indicate that knowledge acquisition, transformation and integration involve successive iterations of codification, abstraction and diffusion of knowledge in relation to product concepts, process requirements and problem-solving approaches. This relates to the capability to adopt, simultaneously, different trajectories in terms of knowledge exploration and knowledge exploitation strategies. The combined adoption of these different strategies enables both strategic and operational flexibility and underlies the successful realisation of absorptive capacity.